Reframing the Management of Irritable Bowel Syndrome: Investigating the Efficacy of a Modified Low Fodmap Diet Approach on Symptom Response - Tara Howley; Lorraine Cooney; Suzanne L Doyle (SURE Journal: (Science Undergraduate Research Experience Journal))
Background/ Objectives: Irritable bowel syndrome (IBS) is a disorder of gut-brain interaction with a multi-faceted pathogenesis. A diet low in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs), known as a low FODMAP diet (LFD), is an effective management option for many, however, it is complex, costly, and restrictive. A milder, modified low FODMAP diet (MLFD) is one suggested alternative, however, data on this approach is lacking. This study aimed to explore the efficacy of a MLFD versus a LFD on symptom improvement in IBS. Subjects/ Methods: Routine clinical data collected on individuals with a Rome IV IBS diagnosis between August 2018 and October 2022 from a specialist-dietitian led IBS clinic in Blackrock Health, Dublin was retrospectively analysed. Individuals had been recommended to follow a LFD or a MLFD for four weeks. Information on symptoms was collected using a modified gastrointestinal symptom rating scale (mGSRS) at initial assessment and at 4-week follow-up. Data was analysed using SPSS. Results: Data on 108 individuals was available; 63 were recommended to follow the LFD, 45 the MLFD. Both the MLFD and LFD achieved significant improvements in mGSRS scores (p Conclusion: The MLFD was associated with significant improvements in symptoms of IBS and normalised stool type. These findings suggest that such stringent restriction as seen in the LFD is not necessary as management options evolve. The future of IBS therapy should consider more liberalised approaches.